The AC/AG Diplotype for the 118A>G and IVS2 + 691G>C Polymorphisms of OPRM1 Gene is Associated with Sleep Quality Among Opioid-Dependent Patients on Methadone Maintenance Therapy. Issue 1 (June 2016) - Zahari, Zalina; Lee, Chee; Ibrahim, Muslih; Musa, Nurfadhlina; Mohd Yasin, Mohd; Lee, Yeong; Tan, Soo; Mohamad, Nasir; Ismail, Rusli
Abstract Introduction Methadone is a full agonist of the opioid receptor mu 1 which is encoded by the OPRM1 gene. Sleep disorders were frequently reported by opioid-dependent patients during methadone maintenance therapy (MMT). It is possible, therefore, that genetic polymorphisms inOPRM1 influence sleep quality among patients on MMT. This study investigated the association ofOPRM1 polymorphisms with sleep quality among opioid-dependent patients on MMT. Methods The sleep quality of 165 male opioid-dependent patients receiving MMT was evaluated using the Pittsburgh Sleep Quality Index (PSQI). DNA was extracted from whole blood and subjected to polymerase chain reaction (PCR) genotyping. Results Patients with IVS2 + 691 CC genotype had higher PSQI scores [mean (SD) = 5.73 (2.89)] compared to those without the IVS2 + 691 CC genotype (IVS2 + 691 GG/GC genotype) [4.92 (2.31)], but the difference did not reach statistical significance (p  = 0.081). Patients with combined 118 AA genotype and IVS2 + 691 GC genotype (AC/AG diplotype) had significantly lower PSQI scores [mean (SD) = 4.25 (2.27)] compared to those without the diplotype [5.68 (2.77)] (p  = 0.018). Conclusion Our study indicates that the AC/AG diplotype for the 118A>G and IVS2 + 691G>C polymorphisms of OPRM1 gene is associated with better sleep quality among males with opioid dependence on MMT.